Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s13760-021-01612-6
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis at the crossroad of COVID-19: focus on immunological and respiratory interplay

Abstract: Coronavirus disease 2019 (COVID-19), a disease caused by the novel betacoronavirus (SARS-CoV-2) has become a global pandemic threat. COVID-19 caused by SARS-CoV-2 is reported to originate in December 2019 in Wuhan, China and spreading rapidly around world. SARS-CoV-2 is structurally similar to the other coronaviruses, causing the severe respiratory syndrome (SARS-CoV) and the middle east respiratory syndrome (MERS-CoV), both binding to the angiotensin-converting enzyme 2 (ACE2) receptor to enter human cells. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 76 publications
(172 reference statements)
0
35
0
Order By: Relevance
“…Sometimes this condition requires hospitalization for potentially lethal exacerbations that may be triggered by infections, stress, and vaccines [ 2 , 3 ]. Hence, the recent SARS-CoV-2 outbreak has led to several critical issues in the management of MG patients [ 4 , 5 , 6 , 7 ]. The first concern arises because many drugs used in the first phase of the Coronavirus Disease 2019 (COVID-19) pandemic (e.g., azithromycin, chloroquine, and hydroxychloroquine) are contraindicated in MG [ 8 , 9 ], with detrimental effects on these patients—there can be clinical worsening until myasthenic crisis in such cases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes this condition requires hospitalization for potentially lethal exacerbations that may be triggered by infections, stress, and vaccines [ 2 , 3 ]. Hence, the recent SARS-CoV-2 outbreak has led to several critical issues in the management of MG patients [ 4 , 5 , 6 , 7 ]. The first concern arises because many drugs used in the first phase of the Coronavirus Disease 2019 (COVID-19) pandemic (e.g., azithromycin, chloroquine, and hydroxychloroquine) are contraindicated in MG [ 8 , 9 ], with detrimental effects on these patients—there can be clinical worsening until myasthenic crisis in such cases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bene cial effect of IL-6 inhibitors in Covid-19 infection can be explained with hypothetical mechanisms by which viral antigens can stimulate production of cytokines, like IL-6, responsible for migration neutrophils in the lung, resulting in alveolar damage. These cytokines are responsible for utility to differentiation of B cells into plasma cells when production of autoantibodies is ampli ed in patients with MG [17]. Three presented MG patients developed renal insu ciency and decrease in saturation accompanied by an increase IL-6 during Covid-19 infection.…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…In a survey of about 11,000 COVID-19 patients, 2 new MG patients were found ( Yuksel et al, 2021 ). The mechanism may be related to the immune disorder and inflammation caused by infection ( Galassi and Marchioni, 2021 , Qin et al, 2020 ). Research on MG patients infected with COVID-19 showed that among 3558 MG patients, 34 patients (0.96%) were infected with COVID-19 ( Solé et al, 2021 ).…”
Section: Nervous System Diseases Related To Sars-cov-2mentioning
confidence: 99%